1998
DOI: 10.2307/3579792
|View full text |Cite
|
Sign up to set email alerts
|

Induction of an Adaptive Response against Spontaneous Neoplastic Transformation In Vitro by Low-Dose Gamma Radiation

Abstract: An adaptive response against spontaneous neoplastic transformation in vitro induced by low-dose gamma radiation has recently been reported using a clone of C3H 10T1/2 cells with a predisposition toward spontaneous transformation (Azzam et al., Radiat. Res. 146, 369-370, 1996). To test the generality of this observation, the HeLa x skin fibroblast human hybrid cell system was used to look for such an adaptive response using a similar experimental protocol. In the experimental protocol used, the frequency of neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 16 publications
8
103
0
Order By: Relevance
“…Considerable additional data also indicate that, at low doses and dose rates of low Linear Energy Transfer (LET) radiation, the LNT assumption of linearity is invalid because risk is overestimated. All these other data show that low doses induce an adaptive response that reduces rather than increases risk at the molecular, cellular, and whole-animal levels (Olivieri et al, 1984;Azzam et al, 1992Azzam et al, , 1994aAzzam et al, , 1994bAzzam et al, , 1996Rigaud et al, 1993;Ishii et al, 1996;Redpath and Antoniono, 1998;Broome et al, 1999;Mitchel et al, 1999b), and does so at doses relevant to human occupational exposure. The mechanisms of these adaptive responses are the subject of intense investigation, but the discussion presented here implicates bystander effects as playing a large role in the adaptive response to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable additional data also indicate that, at low doses and dose rates of low Linear Energy Transfer (LET) radiation, the LNT assumption of linearity is invalid because risk is overestimated. All these other data show that low doses induce an adaptive response that reduces rather than increases risk at the molecular, cellular, and whole-animal levels (Olivieri et al, 1984;Azzam et al, 1992Azzam et al, , 1994aAzzam et al, , 1994bAzzam et al, , 1996Rigaud et al, 1993;Ishii et al, 1996;Redpath and Antoniono, 1998;Broome et al, 1999;Mitchel et al, 1999b), and does so at doses relevant to human occupational exposure. The mechanisms of these adaptive responses are the subject of intense investigation, but the discussion presented here implicates bystander effects as playing a large role in the adaptive response to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The dose rates considered in our studies are, however, much lower than the ones used by Azzam et al (1996) and Redpath and Antoniono (1998). Data on MN formation in human fibroblasts after various priming doses of ϕ-radition followed by a challenge dose show that any priming dose from 1 to 500 mGy (delivered at 1-3 mGy/min) produced the same drop in MN frequency (Broome et al, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…Redpath and Antoniono (1998) showed that this occurred between 100 and 300 mGy for TF/SC in human cells. Azzam et al (1996) found that it was above 100 mGy in rodent cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cultured human cells, this protective effect was observed up to 24 hours after the low dose exposure, and longer in animal models. These low dose exposures have been shown to decrease the spontaneous levels of DNA damage, and spontaneous transformation frequency in different cell lines (Azzam et al, 1996;de Toledo et al, 2006;Redpath and Antoniono, 1998;Redpath et al, 2001). Recently the role of free radicals has been shown to be involved in low dose, low dose-rate, adaptive response mechanisms via oxidative metabolism and DNA repair.…”
Section: Radiation Risk and Low Dose Adaptation Part 2 (Drs Azzam Yamentioning
confidence: 99%